A Recyclable and Highly Effective Sulfamic Acid/EtOH Catalytic System in Synthesis and Natural Product Chemistry of Lignan Compounds - Ali, Z.; Deo, S.; Inam, F. (Asian Journal of Chemistry, 2012)
The utilization of green chemistry techniques is dramatically reducing chemical waste and reaction times and has recently been proven in several organic syntheses and chemical transformations. To illustrate these advantages sulphamic acid is used as a novel recyclable heterogeneous catalyst in the cyclization of Perkin condensation product a-arylidine-b-benzoyl propionic acid to achieve biologically potent 1-phenylnaphthalene system and pericarbonyl lactone lignans under two experimental conditions i.e., conventional and microwave irradiation. The generality of this protocol has been demonstrated by synthesizing a variety of substituted 1-phenyl-naphthalene systems in excellent yields, short reaction time and with good purity.